Pensamento computacional : uma ferramenta potencializadora no processo de representação em crianças na fase pré-operatória - Alves, Emanuela Schmidt (2022)
This work was guided by the following research question: What is the role of computational thinking in the development of the representation process in children in the preoperative phase? As an objective, an attempt was made to investigate, based on Jean Piaget's research, the development of cognitive schemes in the stages of intelligence development classified by age group, focusing on children from 4 to 6 years old, classified in the preoperative phase. By observing the amplification of the representation process that occurs in this phase, and due the importance of these skill for child development, we sought to understand how to use computational thinking to enhance it, and becomes the learning more effective. Several concepts relevant to the area were presented to the children, aiming to observe how Unplugged Computing (a way of developing Computational Thinking without the use of digital means) could significantly help in the development of the preoperative phase. The hypothesis adopted that, through Unplugged Computing, the subject-child, due to the need to acquire more abstract concepts through concrete means, could have access to visual and motor stimuli, additionally to understand contents necessary to develop logical thinking. An exploratory-descriptive methodology was used to conduct the research, consisting of observations of a group of children between the ages of 4 and 6 from a private school in Passo Fundo, RS. Based on this methodology, Unplugged Computing activities were proposed and divided into analysis categories. With this resource, the aim was to identify the development of the concepts of computational thinking through its pillars (abstraction, automation, and analysis) and how these potentialized the representation process in these subjects. Ultimately, the research made it possible (a) to understand the development of each of the children, as they carried out and built their logical thinking during each suggested activity, especially through their interaction and the construction of their learning in the development of the suggested proposals and carried out with the class in the field work, (b) to improve and redefine the concepts on the subject for its author, as an educator and researcher.